Dual roles of NRF2 in tumor prevention and progression: possible implications in cancer treatment - Moon, EJ; Giaccia, A (Elsevier, 2014)
The cap’n’collar (CNC) family serves as cellular sensors of oxidative and electrophilic stresses and shares structural similarities including basic leucine zipper (bZIP) and CNC domains. They form heterodimers with small MAF proteins to regulate antioxidant and phase II enzymes through antioxidant response element (ARE)-mediated transactivation. Among the CNC family members, NRF2 is required for systemic protection against redox-mediated injury and carcinogenesis. On the other hand, NRF2 is activated by oncogenic pathways, metabolism, and hypoxia. Constitutive NRF2 activation is observed in a variety of human cancers and it is highly correlated with tumor progression and aggressiveness. In this review, we will discuss how NRF2 plays dual roles in cancer prevention and progression depending on the cellular context and environment. Therefore, a better understanding of NRF2 will be necessary to exploit this complex network of balancing antioxidant pathways to inhibit tumor progression.